The Main Directions and Priorities of the Unified Transport Policy in the EAEU - TUMANOV, Eldar V.; SPEKTOR, Asiya A.; PANKO, Julia V.; STEPANYAN, Tamara M.; KOMOV, Mikhail S. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
Study of the main directions and priorities of the unified transport policy of the Eurasian Economic Union (EEC). The methodological basis for the study of the problem was the methods of system analysis and synthesis, logic, comparison, systematization, generalization, economic and statistical methods of analysis and data processing, which allowed a comprehensive study of the processes of transport integration of the EAEU. The analysis of Russian and foreign scientific sources on the place and role of transport, transport system, transport policy in the improvement of global economic relations of regional economic associations. Focuses on the practice of the EEC and the EAEC. The key determinants on which the process of formation and development of a single transport space within several countries depends, as well as barriers to this process, are outlined. The analysis of the effectiveness of the implementation of the initiative to conduct a unified transport policy of the Eurasian Economic Union, formulated the main problems and obstacles that may subsequently have a negative impact on the effectiveness and efficiency of the tasks and priorities of the Eurasian coordinated (harmonized) transport policy. Recommendations to reduce and eliminate this negative impact are proposed.